(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The informal use of generative artificial intelligence (AI) tools such as ChatGPT, Copilot, and Gemini is spreading rapidly across workplaces, outpacing institutional governance. This trend—known as Bring Your Own AI (BYOAI)—creates tensions between innovation, trust, and regulatory oversight. This study examines how organizations can manage unsanctioned AI use through a two-phase approach: a systematic review of 45 peer-reviewed studies and a multi-region survey of 345 professionals across business, healthcare, education, and government sectors. Findings reveal six behavioral user archetypes and four organizational governance postures shaped by risk perception and task sensitivity. The paper proposes the BYOAI-Gov™ framework, a behavior-aware model that integrates task-risk zoning (Enable, Regulate, Restrict) with a four-level maturity scale. It reframes informal AI use as a governable organizational behavior and provides practical guidance for balancing innovation with accountability and ethical assurance in decentralized digital workplaces.